Study of proteases activity during larval development of Chilo partellus (Swinhoe). - P, Nalawade S (Recent Research in Science and Technology, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –> Chilopartellus is one of the most serious maize stem borer.The larval developmental period is of 28 days. The acidic, Neural and alkaline proteases activity during larval development of Chilopartellus have been studied. The partial characterization of acidic alkaline and neutral proteases during larval development of Chilo partellushas been also studied.The Sharp increase in acidic, alkaline, neutral proteases activity was noted on the onset of each instar. Then gradual decrease in enzyme activity was observed at the end of each instar. The physiological significance of proteases during larval development of Chilopartellus is discussed.